YouTube channel of the Eurasian National University: issues of efficiency improvement - Mamankul А.Ә.; Aldabergenova Ж.Ж.; Yessenbekova Ұ.М. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2022)
The article studies and evaluates the effectiveness of using the Eurasian National University YouTube channel. The rating list of Kazakhstani content on the YouTube channel is studied. The number of steps for ENU’s YouTube channel to be included in this list has been determined, and the necessary measures have been proposed to achieve this goal. It is planned to increase the effectiveness and expand the scope of use of YouTube video services for the development of cultural and spiritual values of the nation.